Effectiveness of product placement in TV Shows - Dietrich, Felix (2016)
Submitted by Pedro Cabeça (pedro.cabeca@universidadeeuropeia.pt) on 2016-12-16T19:23:24Z No. of bitstreams: 1 Dissertação Mestrado - Felix Dietrich 214015.pdf: 6116197 bytes, checksum: 45ea15198196aaf3b6193e5e7b6646a5 (MD5)